MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATA KULIAH PENGETAHUAN LINGKUNGAN BAGI MAHASISWA BIOLOGI STKIP HAMZANWADI SELONG MELALUI TAHAPAN KEGIATAN LESSON STUDY - Marhamah, Marhamah; Al Muhdhar, Mimien Henie Irawati; Susilo, Herawati; Ibrohim, Ibrohim (Universitas Sebelas Maret, 2014)
Knowledge of the environment is one of the first-year course that must be taken by students of Biology Education Program in STKIP Hamzanwadi Selong. So far, the knowledge of the environment course was conducted using conventional methods that did not train students' critical thinking skills. In an effort to improve the quality of the course, research has been done using PBL and GI methods that aim to improve students' critical thinking skills in biology STKIP Hamzanwadi Selong through the stages of Lesson Study activities. This research is a qualitative descriptive study. The subjects were 75 second semester Biology students of academic year 2012/2013 consisting of three classes. Lesson Study is conducted in class II B for four cycles, each cycle consisting of Plan, Do and See phases. The results of each cycle reflecting on learning in class II B was applied to the class II A and II C. The instrument to measure critical thinking skills using analytical test which refers to the SOLO taxonomy. Based on the data analysis, the descriptive results showed that pretest critical thinking skills of students as a whole are 86.67% in prestructural stage and 13.34% in unistructural stage. While the post-test results of students' critical thinking skills in overall 69.34% were in prestructural stage, 29.34% were in unistructural stage and 1.34% at the multistructural stage. Based on the data obtained, it is known the critical thinking skills have increased by 17.34% after applying PBL learning models combined with GI. Learning through PBL models combined GI train students to solve environmental problems encountered in investigative activities that can improve critical thinking skills. Keywords : Lesson Study, critical thinking, combined PBL- GI